Initial Proteomic Identification of Secreted Proteins of White-Rot Fungus Porodaedalea pini Grown on Liquid Medium - Sunardi; Nakamura, Ayana; Ishiguri, Futoshi; Yokota, Shinso (Asian Journal of Chemistry, 2017)
Porodaedalea pini is a white-rot fungus that attacks conifers and secretes different kinds of extracellular enzymes. To our best of knowledge, this is the first report identifying the secreted proteome of P. pini grown on liquid medium. Some proteins involved in carbohydrate metabolism were identified by peptide mass fingerprinting (PMF) using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI/TOF/MS). The identified proteins were classified according to their biochemical roles as carbohydrate transport and metabolism, amino acid transport and metabolism, aromatic compound metabolism and oxidative stress responses, cellular processes and signaling and hypothetical proteins. Furthermore, one spot of the proteins in the carbohydrate transport and metabolism categories may be correlated to the hydrolytic enzymes secretion. This protein was homologous to the glycoside hydrolase family 1 and seems to be a b-glucosidase.